2008
DOI: 10.1098/rspb.2007.1544
|View full text |Cite
|
Sign up to set email alerts
|

A quantitative test of the relationship between parasite dose and infection probability across different host–parasite combinations

Abstract: Epidemiological models generally assume that the number of susceptible individuals that become infected within a unit of time depends on the density of the hosts and the concentration of parasites (i.e. mass-action principle). However, empirical studies have found significant deviations from this assumption due to biotic and abiotic factors, such as seasonality, the spatial structure of the host population and host heterogeneity with respect to immunity and susceptibility. In this paper, we examine the effect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
140
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 89 publications
(152 citation statements)
references
References 37 publications
12
140
0
Order By: Relevance
“…Both trends have been observed before in this experimental system (39), as well as for other plant viruses (11,20). Moreover, these trends appear to be quite general, since they also appear in other experimental systems (4,28,36,40), where it must be noted that a higher variance in the distribution of founders is equivalent to an increase in mixed-genotype infection frequency (36). Thus, although deviations from the model were not in themselves suffi- FIG 2 Dose-symptomatology relationship at 6 dpi.…”
Section: Resultssupporting
confidence: 61%
See 1 more Smart Citation
“…Both trends have been observed before in this experimental system (39), as well as for other plant viruses (11,20). Moreover, these trends appear to be quite general, since they also appear in other experimental systems (4,28,36,40), where it must be noted that a higher variance in the distribution of founders is equivalent to an increase in mixed-genotype infection frequency (36). Thus, although deviations from the model were not in themselves suffi- FIG 2 Dose-symptomatology relationship at 6 dpi.…”
Section: Resultssupporting
confidence: 61%
“…Heterogeneity in host susceptibility has been implicated in departures from the IAH model; this model can reasonably account for dose-response and mixed-genotype infection data if the probability of infection is allowed to vary over hosts (4,36).…”
Section: Resultsmentioning
confidence: 99%
“…Although the influence of the environmental [23,24], genotype-by-environment [25,26] and genotype-by-genotype [3,27] interactions has been studied extensively in this system, insights from the stepwise infection process have only recently been incorporated. The recent development of P. ramosa clones, for example, has revealed that parasite susceptibility is highly specific [28] and only certain host-parasite genotype combinations are compatible [29]. Underlying this specificity is the attachment of the spores to the oesophagus of compatible host genotypes, a mechanism that is surprisingly unaffected by environmental variation [19].…”
Section: Introductionmentioning
confidence: 99%
“…First, we employ a clone of P. ramosa (single genotype), not field isolates. Field isolates may contain more than one parasite clone (Jensen et al, 2006;Mouton et al, 2007;Ben-Ami et al, 2008;Luijckx et al, 2011). The use of P. ramosa clones negates the complicating factors intrinsic to mixed infections and allows for a more definitive interpretation of experimental results .…”
Section: Introductionmentioning
confidence: 99%